2014
DOI: 10.1620/tjem.234.7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Beijing Version of the REM Sleep Behavior Disorder Questionnaire (RBDQ-Beijing) in a Mainland Chinese Cohort

Abstract: REM sleep behavior disorder (RBD) is one type of parasomnia characterized by nocturnal complex motor activity associated with dream mentation. Growing evidence has indicated that RBD is a preclinical stage of neurodegenerative diseases. Therefore screening RBD patient is becoming important. The RBD Questionnaire-Hong Kong (RBDQ-HK) is an effective questionnaire to screen RBD patients. However, it is hard to distinguish RBD with the questionnaire from severe OSAS patients, who could mimic some symptoms of RBD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
(31 reference statements)
1
11
1
Order By: Relevance
“…There is a considerable discrepancy among the various cutoffs used, ranging from 10 to 45% for overall and 0.7 to 30% for tonic chin EMG activity, in differentiating RBD cases from controls . Despite possible inter‐rater or intercenter variability, there may be a potential cross‐ethnic difference in EMG activity level, as RBD studies from Asian populations seem to report lower EMG activity levels than those reported in Caucasian subjects . Thus, in this study, we employed a lower cutoff of 10% in our community population (this cutoff was also reported by Consens et al) …”
Section: Discussionmentioning
confidence: 94%
“…There is a considerable discrepancy among the various cutoffs used, ranging from 10 to 45% for overall and 0.7 to 30% for tonic chin EMG activity, in differentiating RBD cases from controls . Despite possible inter‐rater or intercenter variability, there may be a potential cross‐ethnic difference in EMG activity level, as RBD studies from Asian populations seem to report lower EMG activity levels than those reported in Caucasian subjects . Thus, in this study, we employed a lower cutoff of 10% in our community population (this cutoff was also reported by Consens et al) …”
Section: Discussionmentioning
confidence: 94%
“…The RBDQ-HK was developed to evaluate the presence, but also the frequency and severity of RBD ( 13 ). A modified version with added screening questions on severe OSA ( 14 ) and validated language translations are available ( 15 ). The scale covers occurrence and frequency of dreams and nightmares, dream content, vocalizations during sleep, motor behaviors during sleep, injuries during sleep, and sleep disruptions.…”
Section: Accuracy Of Screening Instruments For Rbdmentioning
confidence: 99%
“…Shen et al ( 16 ) reported superior diagnostic accuracy of Factor 2 score compared to total RBDQ score in their total RBD sample as well as in PD and OSA patients. Also, adding two items related to OSA in the modified RBDQ-Beijing scale ( 14 ) resulted in improved specificity and PPV, while excellent sensitivity and negative predictive value (NPV) were retained.…”
Section: Accuracy Of Screening Instruments For Rbdmentioning
confidence: 99%
“…We used RBDQ-HK to determine the occurrence of RBD instead of PSG. However, in order to test the compatibility of RBDQ-HK to the mainland Chinese, a study was carried out at our Sleep Disorder Clinic with 118 PSG-confirmed RBD and 106 non-RBD subjects, and RBDQ-HK gave a sensitivity of 97.1% and specificity of 83.2% [29] . As recall bias cannot be avoided in retrospective studies, especially with regard to nocturnal sleep behaviors, bed partners and caregivers are encouraged to co-answer the questionnaire.…”
Section: Discussionmentioning
confidence: 99%